Anti-Stigma Promotion to Improve Tuberculosis Detection and Referrals: A 9P Marketing Mix Case Study - Dian Ika Anggrai Ningrum; Mahendro Prasetyo Kusumo (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Tuberculosis (TB) referral hospitals frequently face a performance paradox in which treatment success rates improve while case detection and laboratory referrals decline. This study aims to analyze how the integration of the 9P marketing mix influences tuberculosis referral laboratory performance and to explain the imbalance between downstream clinical success and upstream service utilization. A qualitative case study design was employed, using in-depth interviews, observations, and document analysis involving physicians, nurses, laboratory personnel, and promotion officers. Data were analyzed thematically using the nine dimensions of the 9P framework. The findings reveal that strong product quality, competent people, and standardized process elements sustain high cure and treatment success rates. However, weak promotion and public relations strategies, fragmented referral communication, and persistent social stigma significantly constrain case detection and laboratory utilization. The results demonstrate that TB service performance is a systemic organizational outcome shaped by the integration of marketing, policy, and partnership mechanisms rather than clinical excellence alone. This study advances the 9P Marketing Mix as a strategic framework for strengthening infectious disease program performance through integrated anti-stigma communication and referral network optimization.